The mediating effect of organisational culture on academic leadership skills and students’ skill-based learning outcomes in Saudi higher education - Radwan, Omaymah; Razak, Ahmad Zabidi Abdul; Ghavifekr, Simin (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2020)
The current study aims to analyse the direct and significant effect of academic leadership skills on students’ skill-based learning outcomes in selected higher education institution in the Kingdom of Saudi Arabia (KSA). It also aims to analyse the mediating effect of organisational culture on academic leadership skills and students’ skill-based learning outcomes. The study was conducted with a quantitative research methodology by distributing questionnaires contained 97 items to faculty members in Jazan University, Saudi higher education institution. A total of 350 responses were further analysed using the SPSS (V23) and PLS-SEM. Results indicated that academic leadership skills have no direct and significant effect on students’ skill-based learning outcomes in selected higher education institution in the KSA. Results also indicated that organisational culture has a significant mediation effect on academic leadership skills and student’s skill-based learning outcomes in selected higher education institution in the KSA. The present study has the potential to reflect positively on higher education, academic leadership, as well as students in higher education. © 2019, University of Malaya. All rights reserved.